Map of the United States. - Kenyon Company (Des Moines, Iowa) (Kenyon Co., 1912)
Map shows early twentieth century political boundaries, place names, and cities in the United States and territories claimed by the United States. Insets: "Aleutian islands," "West Indies," "Hawaiian Islands," "Map of Alaska," "Map of Panama," "Map of Philippine Islands," "Map of Porto Rico," "Guam," "Wake Id.," "Howland and Baker Is.," and "Tutuila Group." Relief shown by hachures. Scale [ca. 1:7,798,000].